Analisis Hubungan Kesehatan dengan Penggunaan Gadget terhadap Pola Tidur pada Siswa: Literature Review - Bintang Rizki Angeli; Fennisyah Andriani Saragih; Nuriyah Nuriyah; M. Dwi Setiawan; Syahputra Syahputra; Dewi Agustina (Universitas Batanghari Jambi, 2023)
The impact of poor sleep quality, among others, will experience various negative things including being prone to accidents, physical health problems, impaired memory and learning, high risk of obesity and mental health problems. This study aims to determine the relationship between health and the use of gadgets on sleep patterns. In this study, the design used is Literature Review. The method of searching for article data sources was carried out through the Google Scholar database in the 2017-2022 period to retrieve relevant articles published in Indonesian. The results of the six journal studies explain that the use of gadgets can have a major effect on a person's sleep patterns, especially teenagers who should need enough sleep to study. However, things like gadget or gadget addiction have become commonplace among the public. Not even parents can handle such things. In conclusion, gadgets should be a place for children to find out things that can become knowledge, but many are misused by opening applications that are not too important for children of their age. It is expected that parents will supervise children in using gadgets.